MENUJU KELUARGA SEJAHTERA DAN KELUARGA SAKINAH - Irfanullah, Rifqi; Nihayah, Rohatun (Pendidikan Agama Islam (S2), UNSIQ Wonosobo, Jawa Tengah, 2023)
Basically every individual wants a prosperous family. Nevertheless, many factors do affect a person's low level of well-being. Just asa family is the perfect goal for each couple, the perfect family needs a number of factors to achieve that level. The study uses qualitative methods that stand for the reality of events in a direct field, primary data obtained from interviews with families in the Village of Siroto Village Bumitirto District Selomerto Wonosobo District. Secondary data was obtained from books and other sources related to the study. Data obtained from the field is then examined and analyzed and arrived at conclusions.. The study shows that, based on family indicators of prosperity by BKKBN, families in the Siroto Village of Bumitirto District Selomerto Wonosobo District, are still in efforts to increase the family stage and prosper to a higher level. This is because the majority of families still survive the prosperous I stage, as well as the fulfillment of an aspect of the family's assessment by the ministry of religion of RI, the family in the Village of Siroto is lacking in theory and legal understanding and general knowledge. But it is offset by the practices and practices of daily life as well as the tribal life of siroto village.